Student Entrepreneurship Intention amidst the Covid-19 Pandemic: An Extended Systemic Entrepreneurship Intention Model Approach - Okto Aditya Suryawirawan; Suhermin Suhermin; Wiwiek Srikandi Shabrie; Dewi Urip Wahyuni (Jurnal Manajemen dan Kewirausahaan, 2022)
The purpose of this study is to further analyze extended systemic entrepreneurship intention and its effect towards college students in Surabaya. This study used purposive sampling towards 118 college students. This study used partial least square through SmartPLS. The findings of this study are: 1) perceived convenience have a positive significant impact towards entrepreneurial intention, 2) risk tolerance have a positive significant impact towards entrepreneurial intention,3) perceived feasibility does not affect entrepreneurial intention, 4) personal attitude does not affect entrepreneurial intention and lastly entrepreneurial intention have a positive significant impact towards entrepreneurial behavior. This study implies that academic institution needs to further ensure students, that becoming an entrepreneur is still a promising career choice amidst the scarcity of job-vacancy in the current market and job layoffs trend during covid-19 pandemic. This study also implies that students risk tolerance and their positive perception towards entrepreneurship were a distinctive quality, hence the need of the academic institution to further develop their intention to become an entrepreneur after graduation.